Antibiotic prophylaxis for third molar extraction in healthy patients: current scientific evidence - Rodrigues, Willian Caetano [UNESP]; Okamoto, Roberta [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Nazareno dos Anjos Carrijo, Ana Claudia; Almeida, Rafael Santiago de [UNESP]; Melo, Willian Morals de [UNESP] (Quintessence Publishing Co Inc, 2015)
Third molar extraction is one of the most frequently performed procedures in the dental clinic, and it is associated with innumerable trans- and postoperative complications, such as pain, trismus, edema, localized alveolar osteitis, and surgical site infection. Some authors advocate the use of local or systemic antibiotics to reduce the incidence of these postoperative complications. However, several studies have revealed an insignificant gain after using antibiotics. Despite the risks of allergic reactions, toxicity, and the development of resistant microorganisms, about 50% of dentists routinely prescribe the use of prophylactic antibiotics for this purpose. The goal of this paper is to evaluate the scientific evidence that justifies antibiotic prescription to healthy patients undergoing third molar extraction.
Keywords: Antibiotics; Prophylaxis; Therapeutics; Third molar